Labour demand analysis in the ICT sector: EU countries and Türkiye - ŞİŞMAN, MEHMET (My University, 2023)
This paper is dedicated to specific research on the information and communications technologies (ICT) sector, where the variables determine labour demand in the European Union (EU) and Türkiye. The research aims to clarify the relationships between employment-generating firm growth that represents labour demand and the independent variables identified by the authors. For this purpose, our method analyses the factors affecting labour demand econometrically. In the study, a panel data set of 22 countries, including 21 EU countries and Türkiye, is used for the period of 2014-2019. The results show that there is a positive and significant relationship between employment in the ICT sector and real gross domestic product (GDP) per capita and frequency of internet use. In addition, the results show that the relationship between employment and wage level in the ICT sector is negative and significant. According to the results obtained from the Fixed Effects (FE) model, the elasticity coefficients of the independent variables in the model present for wages (1.53), GDP per capita (3.27) and frequency of internet use (1.60). Finally, we have discussed the results estimated by the Shadow Variable Least Squares (LSDV) method to measure the impact of each country on the overall variability in employment level. As a result of the study, when labour demand is associated with firm employment increase, the countries in the target geography where a significant and positive relationship was found are Belgium, Bulgaria, Croatia, Czechia, Estonia, Finland, Germany, Hungary, Italy, Latvia, Netherlands, Poland, Portugal, Romania, Slovakia, Spain, Sweden, and Türkiye.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Kalkınma İktisadı ve İktisadi Büyüme; Ekonometri; İstatistik; Social Sciences and Humanities; Economics; Development Economics and Economic Growth; Econometrics; Statistics; Sosyal Bilimler (SOC); Ekonomi ve İş; OPERASYON ARAŞTIRMA VE YÖNETİM BİLİMİ; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; OPERATIONS RESEARCH & MANAGEMENT SCIENCE; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Yönetim Bilimi ve Yöneylem Araştırması; Örgütsel Davranış ve İnsan Kaynakları Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Management Science and Operations Research; Organizational Behavior and Human Resource Management; Social Sciences & Humanities; ICT; Marshall Third Rule; Labour demand; EU; Türkiye; Panel data analysis; Fixed effects model; Least squares dummy variables